Analysis of time characteristics, jump patters and technical-tactical skills of beach volley men`s final in Rio Olympics 2016 - Giatsis, G.; Pérez Turpin, J. A.; Haztimanouil, D. (Journal of Human Sport & Exercise, 2020)
In the men`s final of Beach volleyball in the Rio Olympics 2016 Brazil won Italy team with 2-0 sets. The aim of this study was to find the a) timing characteristics, b) distribution of jumps, c) distribution of side-out and counter attacks, d) type of attack. Player's age was 29 ± 3.4 years and height was 196.5 ± 8.5 cm (Blockers = 203 cm, Defenders = 190 cm). A total of 78 points were played in the match (38.39 min). Distribution of rallies was: Serve errors = 7.7%, Aces = 5.1%, Side-outs = 59% and Counter attacks = 28.2%. The work duration was 7.6 ± 4.7 sec while the rest was 26.2 ± 17.7 sec (ratio = 3.5). The work alone duration without serve aces and errors was 8.6 ± 4.3 (ratio = 3). The rest alone without other intervals was 20.3 ± 6.1 (ratio = 2.4). The total number of jumps was 264 (66 ± 22.7 jumps per player) and the distribution of jumps was (Attack = 38.6%, Block = 31% and Servis = 30.3%). The attacks that blocked were 11.8% while the percentage of spikes was 52.8% and the shots was 47.2%. In conclusion, the results are in accordance with other articles concerning high level of beach volleyball. Coaches should use in the training sessions the specific demands of the work and rest ratio and adapt the rally distribution according to percentages occurring during the match and also use the performance indicators of the best teams in the world.